The three little pigs - Bishop, Gavin, 1946- (New York : Scholastic Inc., 1989)
Relates the adventures of three little pigs who leave home to seek their fortunes and how they deal with the big bad wolf.
School Library Journal
Kirkus Review
3.5
K-3
Keywords: Folklore; Pigs -- Folklore; Folklore; Pigs -- Folklore